What if chemistry had won? : An exercise in counterfactuals from the history of science - Maldonado, Carlos Eduardo (2025)
This paper is an exercise on counterfactuals. Against the standard history of science, it claims that modern physics was not triumphant, but chemistry. After a characterization of the way in which classical mechanics thinks, this text argues that such a way is harmful, and it provides reasons. In contrast, he fact that modernity and the contemporary world emerged from chemistry shed brand new lights, languages, approaches, and relations on to the world in general. Had chemistry be the paradigm, the world would have been a much better place, indeed.